Qualification of Fin-Type Heat Exchangers for the ITER Current Leads. Issue 1 (November 2015) - Ballarino, A; Bauer, P; Bordini, B; Devred, A; Ding, K; Niu, E; Sitko, M; Taylor, T; Yang, Y; Zhou, T
Abstract: The ITER current leads will transfer large currents of up to 68 kA into the biggest superconducting magnets ever built. Following the development of prototypes and targeted trials of specific manufacturing processes through mock-ups, the ASIPP (Chinese Institute of Plasma Physics) is preparing for the series fabrication. A key component of the ITER HTS current leads are the resistive heat exchangers. Special R&D was conducted for these components at CERN and ASIPP in support of their designs. In particular several mock-ups were built and tested in room temperature gas to measure the dynamic pressure drop and compare to 3D CFD models.